Martabat Manusia Sebagai Basis Etis Masyarakat Multikultural - Otto Gusti Madung (STF Driyarkara - Diskursus, 2012)
Abstract: Since the issue of the war against global terrorism emerged, the discourse surrounding the concept of human dignity returns as a normative basis for the protection of basic human rights. The term human dignity has existed since the days of ancient Greek philosophy and was further developed in dialogue with medieval Christian theology and the secular thought of modern times. This article places special emphasis on the understanding of human dignity as defined by a secular thinker and exponent of the Enlightenment, Immanuel Kant. The concept of human dignity as developed by Immanuel Kant is rational and transcends the boundaries of religions, cultures and ideologies; therefore it is suitable as a normative basis for a multicultural society. But the article also does not turn a blind eye to some critical observations offered by adherents of particular ethics concerning the Kantian universal ethics. These critical observations emphasize the ethical principle of substantial solidarity in order to overcome the dangers of anonymity in each model of formal ethics. Keywords: Human dignity, multiculturalism, imperative, ethics, human rights. Abstrak: Sejak isu perang melawan terorisme global muncul, wacana seputar konsep martabat manusia kembali menjadi aktual sebagai basis normatif dalam melindungi hak-hak dasar manusia. Istilah martabat manusia sudah lahir sejak zaman Yunani kuno dan dalam perjalanan sejarah berdialog dengan pandangan teologi Kristen Abad Pertengahan serta pemikiran sekular abad modern. Tulisan ini mencoba memberikan penekanan khusus pada pemahaman tentang martabat manusia seperti dirumuskan oleh pemikir sekular abad pencerahan yakni Immanuel Kant. Konsep martabat manusia yang dikembangkan oleh Immanuel Kant bersifat rasional dan melampaui sekat-sekat agama, ideologi dan budaya; sehingga dipandang layak untuk dijadikan basis normatif sebuah masyarakat multikultural. Akan tetapi, penulis juga tidak menutup mata terhadap beberapa catatan kritis yang diberikan oleh beberapa pengikut etika khusus berkaitan dengan etika universal Kant. Catatan-catatan kritis tersebut menekankan aspek solidaritas substansial dalam etika untuk mengatasi bahaya-bahaya anonimitas dalam setiap model etika formal. Kata-kata Kunci: Martabat manusia, multikulturalitas, imperatif, etika, hak-hak asasi manusia.